Predictors of wealth index in Malawi - Analysis of Malawi demographic Health Survey 2004-2015/16 - Kaboni Whitney Gondwe; Rebekah J. Walker; Lucy Mkandawire-Valhmu; Anne Dressel; Emmanuel M. Ngui; Peninnah M. Kako; Leonard Egede (Elsevier, 2021)
Objectives: To examine the wealth index over a decade utilizing Malawi's Demographic and Health (DHS) survey data from 2004, 2010, and 2015/16, and to explore factors that predict higher wealth. Study design: This was a retrospective descriptive study. Methods: The study utilized DHS data from 2004, 2010, and 2015/2016. The total number of participants was 77,194. Linear regression models were used to assess the effects of the predictors. All analyses were conducted in Stata version 13. Results: Findings showed no significant increase in wealth between the survey years. However, significant increases in wealth were associated with smaller family size (−0.09[-0.10, −0.08]), age (0.02[0.02,0.02]), having formal education (0.21[0.18, 0.24]), and living in urban areas (−1.84[-1.98, −1.70]). Differences in wealth also existed among the different ethnic and religious groups with the Chewa reporting less wealth than other groups, and people with any form of religion reporting more wealth than people with no religion. Conclusions: Minimal changes in wealth have occurred in Malawi between 2004 and 2015/16, and sociodemographic, socioeconomic, and cultural factors are associated with wealth in this population.